Symptoms of Post-Traumatic Stress Disorder and Major Depressive Disorder in Veterans of Operations Enduring Freedom/Iraqi Freedom in Comparison With Those Veterans of Other Conflicts. (1st October 2016) - Gros, Daniel F.; Szafranski, Derek D.; Acierno, Ron
ABSTRACT: Limited research exists on comparing psychiatric symptomatology in veterans of Operation Enduring Freedom and Operation Iraqi Freedom (OEF/OIF) and other conflicts. The present study investigated psychiatric symptoms in 238 treatment-seeking veterans. After controlling for demographic differences, participants from OEF/OIF demonstrated a significantly smaller percentage of full diagnosis post-traumatic stress disorder (PTSD), smaller percentage of comorbid depression, and less severe self-reported PTSD intrusions than veterans from other conflicts. The present findings may help to explain previously identified differences in treatment outcome in veterans from OEF/OIF and other conflicts.